Antioxidant Vitamins and Minerals Composition of Fresh Carrot-Cabbage Juice (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
Antioxidants are substances that protect cells from the damages caused by free radicals. Fruit and vegetables are rich in antioxidants and provide important sources of antioxidants. While the quest for an antioxidant supplement is ongoing, this study investigated the antioxidant vitamins and minerals composition of fresh carrot-cabbage juice. Antioxidant vitamins and minerals compositions of the juice were determined by standard methods using spectrophotometry and atomic absorption spectrophotometry (AAS) respectively. The concentration of antioxidant vitamins was found to be in the order; vitamin C > vitamin A > vitamin E. However, manganese has the highest concentration (P < 0.05) among minerals. There is no significant difference between the concentrations of manganese and copper (P > 0.05). The concentration of chromium is significantly lower (P < 0.05) than that of manganese and copper but greater (P < 0.05) than that of zinc. The study showed that fresh carrot-cabbage juice contains a respective concentration of antioxidant vitamins (A, C and E) and antioxidant minerals (Cu, Cr, Mn and Zn). The juice is hence a good source of antioxidant vitamins and minerals and may help complement the antioxidant system of the body.
Keywords: Antioxidant; Carrot; Cabbage; Vitamins; Minerals